Pengaruh Kepemimpinan Kepala Sekolah dan Kelompok Kerja Guru Terhadap Kinerja Guru Sekolah Dasar - Badrudin Badrudin; Teti Muliawati; Yunus Russamsi; Ari Prayoga (Tadbir: Jurnal Manajemen Pendidikan Islam, 2020)
This research is motivated by the problem of the performance of elementary school teachers in the Antapani subdistrict area of ​​Bandung in the face of the problem that the performance of teachers is not yet optimal, it can be seen in the average teacher performance data of 78%. In an effort to improve teacher performance through the Principal's leadership and teacher participation in Teacher Working Group activities. In this research the object of research is the Principal's Leadership (X1) and Teacher Working Group activities (X2) and Teacher Performance (Y). This research uses a quantitative approach while the method used is descriptive research method. The population in this study were 338 elementary school teachers in the Antapani district of Bandung, from 77 elementary schools, the sample in this study was 77 teachers using a proportional stratified random sampling technique. Data collection procedures are carried out by means of observation and questionnaire distribution. In simultaneous testing the level of influence of the Independent variable (Principal Leadership and Teacher Working Groups) on the dependent variable (Teacher Performance) has an influence. This is proven by the Adjusted R figure of 0.570a indicating that Teacher Performance has a relationship between Principal Leadership and Teacher Working Groups categorized as strong with a percentage of 57%, and Fcount> Ftable, which is 17,839> 3.12 with a significance level of 0,000 <0.05, Then Ho rejected means that there is a significant simultaneous effect of the independent variable on the dependent variable or it can be said that there is an influence of the Principal's Leadership and Teacher Working Groups on the Performance of Elementary School Teachers in the Antapani District of Bandung.